2009
DOI: 10.1260/026361709789625270
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption and Movement of Carbofuran in Four Different Soils Varying in Physical and Chemical Properties

Abstract: Laboratory studies were conducted to determine the adsorption and movement of carbofuran on four divergent textured Indian soils at a fixed volume fraction (f s = 0.1) of methanol/water mixtures using batch equilibrium and soil thin layer chromatography (soil TLC) techniques. The measured equilibrium adsorption isotherms for silt loam (FSL and ASL) and loam (KL) soils were L-shaped and for sandy loam (BSL) soil S-shaped, all being well fitted by the Freundlich isotherm. A higher adsorption of carbofuran was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Minerals 2021, 11, x 9 of 18 material evoked a higher affinity of carbofuran to the soil than the addition of humic acids. It was in accordance with studies of Singh and Srivastava, (2009) [73] who found that carbofuran is better correlated with the mineral content of the soils than with their organic matter. Nevertheless, kaolinite's presence in the L soil material had no effect on the carbofuran sorption (22.4%), indicating that other (2:1) clay minerals (illite and montmorillonite) were better pesticide sorbents [62,74] in the studied case.…”
Section: Carbofuransupporting
confidence: 93%
“…Minerals 2021, 11, x 9 of 18 material evoked a higher affinity of carbofuran to the soil than the addition of humic acids. It was in accordance with studies of Singh and Srivastava, (2009) [73] who found that carbofuran is better correlated with the mineral content of the soils than with their organic matter. Nevertheless, kaolinite's presence in the L soil material had no effect on the carbofuran sorption (22.4%), indicating that other (2:1) clay minerals (illite and montmorillonite) were better pesticide sorbents [62,74] in the studied case.…”
Section: Carbofuransupporting
confidence: 93%
“…The higher toxicity observed in cladocerans exposed to leachate dilutions is consistent with the high leaching potential of carbofuran [45,46]. This behavior is due to its high water solubility (322 mg/L), low sorption (K OC $ 23.3 ml/g), and moderate persistence (soil median degradation time (DT50) $ 29 d; aqueous hydrolysis DT50 at 208C and pH 7 $ 37 d; http:// sitem.herts.ac.uk/aeru/iupac/118.htm).…”
Section: Carbofuran Toxicity To Cladoceranssupporting
confidence: 67%
“…The lower toxicity of leachate dilutions, compared with runoff, may be related to the adsorption of some carbofuran to the soil organic matter during its percolation trough the soil profile. Despite this contribution of soil organic matter to pesticide sequestration, the sandy texture seems to have mitigated this effect and increased carbofuran mobility [46].…”
Section: Carbofuran Toxicity To Cladoceransmentioning
confidence: 99%
“…These results were consistent with those of the batch tests, where Freundlich's K F was significantly correlated with soil organic matter and clay (Table 4). Other authors previously found the contents in clay and organic matter to play a key role in carbofuran retention by soils [10,30,37,38]. However, K F was more markedly influenced by organic matter than by clay (Table 4).…”
Section: Stirred Flow Chamber Testsmentioning
confidence: 80%